Epidemiological and clinical characteristics of congenital pseudarthrosis of the tibia in China - Zhou, Yijun; Tan, Qian; Liu, Kun; Liu, Yaoxi; Zhu, Guanghui; Mei, Haibo; Yang, Ge (Frontiers in Pediatrics, 2022)
Background Congenital pseudarthrosis of the tibia (CPT) is a refractory and rare disease. Because of its extremely low incidence, little is known about its clinical features. In this retrospective study, we aim to analyze the clinical characteristics of patients with CPT. Materials and methods This is a retrospective study of children with CPT identified by the radiological review. Investigations of CPT included general conditions, the characteristics of CPT, treatment methods, and surgical complications. Results We collected 514 CPT cases from March 1999 to March 2020 in our hospital, such as 317 (61.67%) boys, 197 (38.33%) girls; 330 (62.86%) in Crawford IV; 510 (97.14%) in mid and distal 1/3 tibia; 481 (93.58%) in less than 3 years at onset age; 297 (57.78%) in less than 3 years at the first outpatient visit. The most common post-operative complication was ankle valgus (101, 39.60%), followed by limb length discrepancy (91, 35.69%), refracture (38, 14.90%), osteomyelitis (15, 5.88%), and removal of internal fixation (10, 3.93%). Conclusions CPT with a higher incidence of Crawford IV frequently occurs in boys and the middle or distal part of the tibia; most patients have the onset age and first outpatient visit before 3 years; the major surgical complications are ankle valgus and limb length discrepancy.